Nigeria's Perpetual Underdevelopment and Theory of Development Policy - Fashola, Mashhud (International Journal of Business and Social Science Research, 2022)
The paper revealed how Nigeria has remained perpetually underdeveloped by various development indicators. To explain Nigeria’s perpetual underdevelopment, the paper presented a Structural Theory of Development Policy. The theory postulates an interrelationship among four components of any economic system, comprising policy instruments (vector x), external exogenous variables (vector u), target and non-targetendogenous variables (vectors y and z), impacting welfare function w(y), as illustrated below:The theory elucidates perpetual underdevelopment by the following obstacles:(i) Perverted articulation of development objectives(ii) Deficient knowledge of the economic system(iii) Excessive vulnerability to external factors(iv) Limited capacity for policy implementation The resolution of these obstacles was discussed. However, the deficient knowledge of the economic system was considered the critical factor for extensive empirical analysis. A classical illustration is the foreign-exchange excess-demand theory, empirically proven to be a false paradigm, inapplicable to the Nigerian economy characterized by overwhelming dependence on primary commodity exports, price and income inelastic demand for goods and services, double-digit inflation rate, severe political instability, and unbridled corruption fuelling capital flight. Comprehensive econometric analysis for Nigeria negated the foreign exchange excess demand theory in all its ramifications, justifying the need for foreign exchange market regulation.